Pengelolaan Limbah Anorganik di Dusun Ajung Kulon Melalui Pelatihan Wasteminaponik Skala Komunal Dusun - Dandi Wahyu Agung Prasetyo; Dimas Kurniyanto; M. Irvan Maulana; Adinda Maharani Dwi Safitri; Febiola Novita Sari; Maria Azizah (Indonesian Journal Publisher, 2024)
Inorganic waste management is a community problem, especially in Jember Regency. Lack of public knowledge about inorganic waste management is still a major problem. People in Ajung Kulon, Ajung village still throw rubbish carelessly, especially in rivers, which has an impact on the environment around residential and agricultural land areas. This community service activity aims to provide knowledge of inorganic waste management to the women recitation group Al-Mukhlisin in Ajung Kulon. Community service activities were carried out with several activities, namely socialization about waste, training and implementation of wasteminaponic cultivation starting from making huts, assembling installations, sowing seeds, planting vegetable, raising fish and harvesting. The implementation of this community service was conducted 2 wasteminaponic installations with 50 planting holes per installation. Implementing this community service can also increase partner competency, including: 1) Increasing knowledge about how to manage inorganic waste, which was initially only 30.7% and increased to 100% after training. 2) Increase partner creativity in managing waste, especially inorganic waste. Partners' interest in wasteminaponic cultivation after training was 100% from 15 respondents. 3) 80% of partners were able to improve their skills regarding science and technology regarding product logo design using a simple application installed on their smartphone. 4) Increase knowledge and skills about good product packaging to increase product selling prices. 5) Partners are able to market products by utilizing their social media, namely WhatsApp, Facebook and Instagram.